Pediatric low-grade glioma in Africa: a baseline study before the implementation of Global Initiative for Childhood Cancer strategies - van Heerden, Jaques; Esterhuizen, Tonya Marianna; Jbebli, Elhem; Fedhila, Faten; Rhayem, Samar; Chabchoub, Imène; Togo, Boubacar; Van Zyl, Anel; Neethling, Beverley; Thomas, Karla; Charlton, Robyn; Ngcana, Thandeka; et al. (Frontiers in Cancer Control and Society, 2025)
IntroductionPediatric low-grade glioma (LGG) is a World Health Organization (WHO) Global Initiative for Childhood Cancer (GICC) index tumor constituting up to a third of pediatric central nervous system (CNS) tumors. The baseline characteristics, survival, and management resources for pediatric LGG in Africa are unknown. We aimed to evaluate the pediatric neuro-oncology multidisciplinary team resources, epidemiology, and survival outcomes of pediatric LGG in Africa to document baseline information prior to GICC implementation.MethodsThe study consisted of two parts: a survey completed by African pediatric oncology units (POU) to evaluate the local resources and a retrospective evaluation of data to determine the 5-year overall survival (OS) for patients under 18 years diagnosed with LGG between 2008 and 2018. Data were described in frequencies and percentages. Survival was expressed with Kaplan–Meier curves.ResultsFive-hundred and eighty-eight patients were included from fifteen POUs in six countries: South Africa (45.9%), Egypt (30.8%), Morocco (12.6%), Mali (4.4%), Tunisia (3.6%) and Uganda (2.7%). The median age was 4.4 years (interquartile range 2.4–7.3 years). The most common primary tumor site was the brainstem (n = 125, 21.3%), the most common histology was pilocytic astrocytoma (n = 270, 47.5%), the majority of tumors (n = 292, 93%) were localized, and 40 (6.8%) patients had neurofibromatosis. Complete resection was obtained in 99 (16.8%) cases, incomplete resection in 179 (30.4%), and no surgery or biopsy only was performed in 310 (52.7%) cases. One hundred and forty-seven (25.3%) of the 580 patients with a documented radiotherapy status, were irradiated, and 320 (54.4%) received chemotherapy. Only 259 (15.3%) patients received chemotherapy of which the most common chemotherapy regimen was vincristine-carboplatin (n = 220, 84.9%). The 5-year OS was 90.5% ± 1.6%. The 5-year OS in Tunisia was 95.1% ± 1.1%, 92.4% ± 2.1% in Egypt, 89.0% ± 3.2% in South Africa, 70.7% ± 6.7% in Morocco and 66.7% ± 15.7% in Uganda (p < 0.001). Four of the 41 (9.8%) responding countries reported having pediatric neuro-oncology subspecialists, and four (9.8%) had national pediatric LGG protocols. In Africa there is one radiotherapy center per 2,235,125 children and one neurosurgeon per 304,685 children, with ~70% of these resources accessible in four countries.DiscussionDue to several resource challenges and developing treatment centers, only fifteen pediatric oncology units from six countries participated. We documented a baseline 5-year OS of 94.9% for LGG in African children. To obtain an accurate estimation of pediatric LGG survival in Africa, increasing participation from a wider range of countries, especially poorly resourced settings, is necessary.